Carabobo Battle : War, political imaginary and nation (Mayéutica Revista Científica de Humanidades y Artes, 2025)
Carabobo is not only the site of one of the main SpanishAmerican battles for Independence. Depending on the interpretation we make of this event, from military history to political history, passing through social history, in addition to being a war event, Carabobo has been the privileged source of our Patriotic History and the matrix of our historical caudillismo. Therefore, beyond the historical romanticism that still dominates the approach to any event related to the War of Independence, our purpose is to take advantage of the commemoration of this event, to try other readings aimed at investigating a process of longer duration, such as the formation of the Venezuelan State and the construction of our idea of Nation, as an imagined political community.
Keywords: Patriotic History; Fiesta; Political Imaginary; Carabobo Battle